A simple automated system for hall effect measurements - Abas, Ariffin; Shaari, Abdul Halim; Talib, Zainal Abidin; Abdul Wahab, Zaidan (Penerbit Universiti Kebangsaan Malaysia, 2012)
This project deals with the development of a computer interfacing technique for the study of Hall effect. A stepper motor with resolution of 0.1 mm was used to move a pair of permanent magnet backward and forward against the sample. The General Purpose Interface Bus (GPIB) card together with a digital nanovoltmeter and teslameter using serial port siri RS232, interface were used to measure the potential difference and magnetic field strength, respectively. Hall effect for YBa2Cu3-xTixO7-δ system (x=0.00, 0.01, 0.03 and 0.05) showed positive sign Hall coefficient showing that the material is a hole type carrier at room temperature. Parameters such as Hall coefficient and charge carrier concentration were also display on the front panel of Lab View programming.